2019
DOI: 10.1097/nne.0000000000000677
|View full text |Cite
|
Sign up to set email alerts
|

DNP Program Faculty and Graduates' Knowledge and Use of QI and Safety Processes

Abstract: Background Across doctor of nursing practice (DNP) programs, wide variation exists for DNP project expectations and curricular integration of Quality and Safety Education for Nurses competencies. Purpose This study examined DNP project characteristics and compared knowledge, skills, and attitudes about quality improvement (QI) processes between DNP program faculty and graduates. Methods This descriptive stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…For DNP students, there is uncertainty regarding differences between forms of inquiry (EBP/QI/research) with many projects containing fatal flaws, diminishing impact, and likelihood of publication. 9,11,26,27 Project ambiguity impacts healthcare organizations, thereby contributing to a perpetual cycle of confusion and inconsistency. 10,28 It is critical that leaders build a cadre of site mentors knowledgeable and competent in various inquiry methodologies serving as a resource for students.…”
Section: Project Road Map Conceptual Clarity and Strategic Alignment ...mentioning
confidence: 99%
See 2 more Smart Citations
“…For DNP students, there is uncertainty regarding differences between forms of inquiry (EBP/QI/research) with many projects containing fatal flaws, diminishing impact, and likelihood of publication. 9,11,26,27 Project ambiguity impacts healthcare organizations, thereby contributing to a perpetual cycle of confusion and inconsistency. 10,28 It is critical that leaders build a cadre of site mentors knowledgeable and competent in various inquiry methodologies serving as a resource for students.…”
Section: Project Road Map Conceptual Clarity and Strategic Alignment ...mentioning
confidence: 99%
“…Correspondingly, there may also be unreasonable expectations and deadlines for healthcare institutional review boards (IRBs) and scholarly projects not conducive to rapid implementation or in alignment with strategic priorities, especially given postpandemic workforce burnout 7,8 . In addition, evidence suggests nursing faculty lack knowledge and proficiency regarding evidence-based practices (EBPs) and quality improvement (QI) methodologies, ultimately describing dissatisfaction with scholarly projects 8,9 . Methodological uncertainty among DNP project–focused publications is pervasive, further contributing to confusion 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a later study of 252 DNP programs in the United States, 117 faculty indicated that they were skilled, but not proficient in quality improvement strategies. In addition, qualitative results found that DNP faculty found the need for quality improvement and QSEN refresher programs (Tovar et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two findings with statistically significant agreement among DNP faculty and graduates were that nurses have an important role in a hospital's QI efforts, and employers expect DNP graduates to be prepared to facilitate health care transformation in their setting. 5 A related finding, which did not reach statistical significance, was that faculty were more likely than DNP graduates to strongly agree that employers expected graduates to be prepared to participate in, but not lead, QI initiatives. This finding highlights the need for more research to identify the level and type of QI preparation that employers desire among DNP graduates.…”
mentioning
confidence: 94%